2021
DOI: 10.3389/fpls.2021.730718
|View full text |Cite|
|
Sign up to set email alerts
|

A Novel Banana Mutant “RF 1” (Musa spp. ABB, Pisang Awak Subgroup) for Improved Agronomic Traits and Enhanced Cold Tolerance and Disease Resistance

Abstract: Banana is a major fruit crop grown in tropical and subtropical regions worldwide. Among cultivars, “FenJiao, FJ” (Musa spp. ABB, Pisang Awak subgroup) is a popular variety of bananas, due to its better sugar-acid blend and relatively small fruit shape. However, because the traditional FJ variety grows relatively high in height, it is vulnerable to lodging and unsuitable for harvesting. In this study, we sought desirable banana mutants by carrying out ethyl methanesulfonate (EMS) mutagenesis with the FJ cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 83 publications
1
6
0
Order By: Relevance
“…The concentration of soluble sugar, proline and other soluble proteins influences the magnitude of impact of chilling injury to plant. This was confirmed by Wang et al (2021) who identified two to eight times higher concentration of soluble sugars and proteins in cold‐tolerant mutant line of banana. This showed that various proteins and transcription factors are involved in complex cellular alterations arisen due to cold stress and thereby regulate signal transduction and different pathways involved in tolerance mechanism.…”
Section: Effects Of Cold Stress On Morphology and Physiology Of Bananasupporting
confidence: 60%
See 2 more Smart Citations
“…The concentration of soluble sugar, proline and other soluble proteins influences the magnitude of impact of chilling injury to plant. This was confirmed by Wang et al (2021) who identified two to eight times higher concentration of soluble sugars and proteins in cold‐tolerant mutant line of banana. This showed that various proteins and transcription factors are involved in complex cellular alterations arisen due to cold stress and thereby regulate signal transduction and different pathways involved in tolerance mechanism.…”
Section: Effects Of Cold Stress On Morphology and Physiology Of Bananasupporting
confidence: 60%
“…The concentration of soluble sugar, proline and other soluble proteins influences the magnitude of impact of chilling injury to plant. This was confirmed by Wang et al (2021) who identified two to eight times higher concentration of soluble sugars and proteins in cold-tolerant mutant line of banana.…”
Section: Physiological Effectmentioning
confidence: 64%
See 1 more Smart Citation
“…After mutagenizing a plant, the first generation of seeds can be selected and selfed in successive rounds to create a large near-isogenic homozygous seed bank ( Till et al., 2003 ). Homozygote is difficult to achieve in obligate vegetative breeding species, such as bananas ( Wang X et al., 2021 ). However, homogeneous populations with fixed heterozygote and common features in all plants can be produced by clonal reproduction.…”
Section: The Application Of Ems Mutagenesismentioning
confidence: 99%
“…In vitro technologies have also contributed to the development of methods for raising virus-free plants, rapid multiplication of elite clones, somatic embryogenesis, soma clonal variation, transgenic plants, and germplasm conservation. In the case of vegetatively propagated plants, multicellular meristems are often employed for undertaking in vitro mutagenesis [53,54]; however, occurrence of chimeras and phenotypic instability are limitations. Somatic embryogenesis, temporary immersion, and plant cell cultures have immense potential for in vitro propagation and genetic transformation in fruit trees such as mango, banana, pistachio, apple, papaya, coffee, and date palm.…”
Section: In Vitro Approachesmentioning
confidence: 99%